Studi Tentang Regulasi Emosi pada Siswa Broken Home di SDN Pradah Kalikendal 3 Surabaya - Christiana, Elisabeth; Sutanto, Tiara Putri (Universitas Muria Kudus, 2024)
This study aims to determine the level of emotional regulation of broken home students in elementary school, emotional regulation factors and the occurrence of broken home, the impact of emotional regulation, the need for guidance and counseling in elementary schools. The research conducted is a type of qualitative research with a case study approach. The subjects in this study were two students aged 8 and 10 years who were broken home students with characteristics of low emotional regulation at SDN Pradah Kalikendal 3 Surabaya. Data collection was carried out using observation, interview and documentation techniques. The results of this study concluded that elementary school students are still not able to control their emotional regulation due to broken home due to age factors where the use of some coping by venting negative behavior. Researchers conducted interviews first with all homeroom teachers in grades 1-6 before observing and interviewing students who experienced broken homes with lack of emotional regulation control at SDN Pradah Kalikendal 3 Surabaya.